The Oslo conspiracy : a thriller - Skredderberget, Asle, 1972- (Thomas Dunne Books, 2016)
"The main character in Asle Skredderberget's crime novels is Milo Cavalli. Half Norwegian and half Italian, he is definitely not your typical depressed Nordic noir investigator. In fact he's quite the opposite. Milo is successful and attractive AND extremely rich. He goes to confession. He worries about his friends and family. And he taps into his family fortune whenever he needs to in order to crack the case he's working on. In The Oslo Conspiracy, a scientist is found dead in a hotel room in Rome. Before she is strangled, she manages to scribble a few words on a piece of paper. Milo Cavalli is sent to help out with the investigation in Italy, since he is familiar with Italian red tape. Milo finds the note from the scientist, and he also learns that earlier her kid brother had been executed by gang members in a schoolyard. Milo becomes obsessed with finding out if there is a link between the two killings -- the sister strangled in Italy and the brother shot in Norway. And he is willing to use his vast fortune and special connections -- especially when those connections involve beautiful women -- to find the answers. A new twist in thrillers, The Oslo Conspiracy is certain to captivate readers who like their heroes rich, handsome, caring, and very, very sexy."--